Comparing efficacy and side effects of two systemic chemotherapy regimens for eye‐preserving therapy in children with retinoblastoma. Issue 2 (4th October 2021) - Grümme, Lea; Biewald, Eva; Reschke, Madlen; Fischhuber, Karen; Hanbücken, Anna; Schlüter, Sabrina; Müller, Bert; Kiefer, Tobias; Göricke, Sophia; Geismar, Dirk; Ryl, Tatsiana; Sirin, Selma; et al.
Abstract: Background: Eye‐preserving therapy in retinoblastoma comprises systemic chemotherapy, but studies analyzing the efficacy of different chemotherapy regimens are scarce. Methods: The efficacy and side effects of two different eye‐preserving chemotherapy regimens containing either vincristine, etoposide, and carboplatin (VEC) or cyclophosphamide, vincristine, etoposide, and carboplatin (CyVEC) were compared in a prospective non‐interventional observational study including children diagnosed with retinoblastoma between 2013 and 2019 in Germany and Austria. Event‐free eye survival (EFES) and overall eye survival (OES) of all 164 eyes treated with both regimens and risk factors were investigated. Results: The EFES after VEC (2‐year EFES 72.3%) was higher than after CyVEC (2‐year EFES 50.4%) ( p logrank  < .001). The OES did not differ significantly between the two treatment groups ( p logrank  = .77; 2‐year OES VEC: 82.1% vs. CyVEC: 84.8%). Advanced International Classification of Retinoblastoma (ICRB) group was prognostic for a lower EFES ( p logrank  < .0001; 2‐year EFES ICRB A/B/C 71.3% vs. ICRB D/E 43.0%) and OES ( p logrank  < .0001; 2‐year OES ICRB A/B/C 93.1% vs. ICRB D/E 61.5%). The multivariate analysis showed that age at diagnosis older than 12 months and ICRB A/B/C were associated with better EFES. No second malignancies or ototoxicities were reported after a follow‐up of median 3.1 years after diagnosis of retinoblastoma (range 0.1–6.9 years). Conclusions: Despite omitting cyclophosphamide, the EFES was higher after VEC chemotherapy that contains higher doses of carboplatin compared to CyVEC. The major risk factor for enucleation was advanced ICRB tumor grouping. Randomized clinical trials on efficacy and side effects of eye‐preserving chemotherapy are required to tailor treatment protocols for retinoblastoma patients.